A multi-resolution SPH-FEM method for fluid–structure interactions - Chen, Cheng; Shi, Wen-Kui; Shen, Yan-Ming; Chen, Jian-Qiang; Zhang, A-Man (Computer methods in applied mechanics and engineering, 2022)
This work presents a multi-resolution fluid–structure interaction (FSI) solver for hydroelastic issues by coupling the Weakly Compressive Smoothed Particle Hydrodynamics (WCSPH) method and the Finite Element Method (FEM). The fluid is simulated by the SPH method, and the structure response is considered by the FEM beam. The normal flux method is employed to calculate the coupled force between the fluid and structure by considering the surface integration term in SPH approximation equations. A multi-resolution technology is proposed by discretizing the fluid and structure with different resolutions. The resolution of beam elements can be either coarser or finer than that of SPH particles. Finally, the accuracy, robustness and efficiency of the current FSI solver are strictly validated by several typical benchmarks, including the hydrostatic, free-surface flow and water entry problems. •We developed a coupled SPH-FEM method for fluid–structure interactions.•Different spatial–temporal resolution is employed for fluid and solid structure.•The accuracy, efficiency, and robustness of the FSI solver are strictly validated.